Design and motion control of a spherical robot with control moment gyroscope - Jiazhen Chen; Ping Ye; Hanxu Sun; Qingxuan Jia (2016 3rd International Conference on Systems and Informatics (ICSAI), 2016)
Despite much work has been done to study and develop different types of spherical robots in the recent years, there are few practical applications. Limited by the totally enclosed spherical shell and the special walking style of rolling, existing spherical robots usually lack exteroceptive sensors, such as laser, vision camera and sonar. So they have weak capability of environmental perception and low precision of motion control. This paper presents a spherical robot carrying a Control Moment Gyroscope (CMG) group. The robot aims to have greater ability to cross obstacles and climb up slopes, and it will have a more stable platform for sensors to enhance the environmental perception. The mechanical structure of the spherical robot is introduced. Under reasonable assumptions, simplified dynamic model is developed as well. The motion control of the robot with CMG group is studied by simulations. Simulation results validate the feasibility of the structure design. The work presented here is a step towards the overall goal of an autonomous spherical robot.